Analysis of Science Learning Problems in Junior High School Community Learning Center Holy Trinity, Sabah-Malaysia - Winda Mandasari; Novi Ratna Dewi; Sri Sukaesih (Jurnal Penelitian Pendidikan IPA, 2025)
This study is a descriptive study with a qualitative approach that aims to explore in depth the factors causing science learning difficulties in students at CLC Holy Trinity. Data collection techniques used questionnaires and interviews to obtain comprehensive data on students' learning experiences. The results of the study indicate that students' learning difficulties are influenced by several main factors, namely less varied learning methods, minimal use of interactive learning media, and a less supportive learning environment. Although some students show sufficient interest in science lessons, many of them find it difficult to understand basic concepts such as force, motion, and energy, especially during independent learning. These findings emphasize the importance of the role of teachers in creating an interactive and enjoyable learning atmosphere, as well as the need to provide relevant learning media. Collaboration between schools, teachers, and parents is needed to overcome these learning barriers. This study is expected to be an input in developing more effective and adaptive learning strategies to the needs of students in the CLC environment.